MSU online clearance system for graduating student - Mhandu, Greatman (Midlands State University, 2020)
The project outlines and gives support for the Online Clearance System for Graduating Student which was developed as a final year Project at the Midlands State University. The system has been developed for Midlands State University and it is a web based to cater for technological rapid changes. The research was guided by seven objectives; to develop a platform that facilitate information exchange between the clearance information units (the Library, Student Accounts and Departmental) and the graduating student. This enables both the student and clearance staff to clearly communicate upon the clearance process. Secondly, to develop a system that allows the graduating student to fill the transcript request form online. Geographical barriers are alleviated as the student can be able to commence the process of clearance as long as the student is using an internet able access device. To develop a system that allows the student to send issue requests on the academic fixed information. In the event that a module was added or removed by mistake, the student can be able to request for such corrections online. To develop a system that enables the student to check the clearance status online. This enables the student to actually see how far the clearance process have going without the even coming physically to the clearance departments. Provided that the student has been successfully cleared, the ticks will be shown on each respective department. To develop a system that allows the clearance sections to flight requirements as well as sending messages to the student. The author used research instruments such as Dreamweaver, MySql, Php, Apache and Wamp server. In addition to this, some information gathering methodologies such as the interviews, observations as well as questionnaires were used. Finally the new system was implemented using parallel conversion method.